2022
DOI: 10.3390/polym14081627
|View full text |Cite
|
Sign up to set email alerts
|

Can 3D-Printed Bioactive Glasses Be the Future of Bone Tissue Engineering?

Abstract: According to the Global Burden of Diseases, Injuries, and Risk Factors Study, cases of bone fracture or injury have increased to 33.4% in the past two decades. Bone-related injuries affect both physical and mental health and increase the morbidity rate. Biopolymers, metals, ceramics, and various biomaterials have been used to synthesize bone implants. Among these, bioactive glasses are one of the most biomimetic materials for human bones. They provide good mechanical properties, biocompatibility, and osteointe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 110 publications
(139 reference statements)
0
12
0
Order By: Relevance
“…Bioactive glass (BG) has emerged as a promising alternative material for 3D-printed scaffolds due to its demonstrated osteoconductivity and biocompatibility, and it is widely utilized as both a drug-delivery system and as a component of implants [ 170 , 171 ]. BG can be used as a raw material for a variety of 3D printing techniques, including SLS, SLA, and FDM [ 171 ].…”
Section: Future Directions For Addressing Bone Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioactive glass (BG) has emerged as a promising alternative material for 3D-printed scaffolds due to its demonstrated osteoconductivity and biocompatibility, and it is widely utilized as both a drug-delivery system and as a component of implants [ 170 , 171 ]. BG can be used as a raw material for a variety of 3D printing techniques, including SLS, SLA, and FDM [ 171 ].…”
Section: Future Directions For Addressing Bone Lossmentioning
confidence: 99%
“…Bioactive glass (BG) has emerged as a promising alternative material for 3D-printed scaffolds due to its demonstrated osteoconductivity and biocompatibility, and it is widely utilized as both a drug-delivery system and as a component of implants [ 170 , 171 ]. BG can be used as a raw material for a variety of 3D printing techniques, including SLS, SLA, and FDM [ 171 ]. Tulyaganov et al demonstrated the effectiveness of 3D-printed silica-based BG in forming hydroxyapatite within simulated body fluid (SBF), as well as an in vivo 4.5 mm rabbit femoral defect model, in which the 3D-printed BG scaffolds resulted in osseous defect healing and the formation of new bone [ 172 ].…”
Section: Future Directions For Addressing Bone Lossmentioning
confidence: 99%
“…Apatite powders on their own do not possess consolidation behavior that enables printability, thus it is necessary to optimize bio-inks to achieve final devices with appropriate mechanical integrity through the combination of CaP powders with polymer materials, as they possess sufficient mechanical properties and are suitable for the repair of critical bone defects [ 79 ]. In this latter aspect, various biocompatible polymers, such as polylactic acid (PLA), poly(lactic-coglycolic acid) (PLGA), and polycaprolactone (PCL) have been used for the fabrication of bone implants and even received approval from the US FDA as materials for 3D printing of biomedical implants [ 80 ]. Among them, polylactic acid (PLA) has been defined as a biomaterial with potential clinical applications in many studies due to its slow degradation properties and reliable biocompatibility [ 81 ].…”
Section: Translation Of the Biomimetic Concept To 3d Scaffold Develop...mentioning
confidence: 99%
“…In a previous study of our team, we probed the successful control of the interfacial bonding of multimaterial systems fabricated by this technique. 32,33 Despite the interesting papers dedicated in the recent years to 3D printing process (specially to FDM 34 ), there is an aperture to DPPmE and its adaptation to develop innovative FGM devices for medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, it is necessary to pay special attention to control the rheological properties of molten materials (like viscosity modulus, zero-shear viscosity, or relaxation time/elasticity) during extrusion through the nozzle and after deposition in order to ensure good interlayer welding and the mechanical robustness of 3D-printed parts. , Further, some DPPmE systems present an extrusion system with multiple screws, resulting in FGM-printed parts with different material composition and architecture. In a previous study of our team, we probed the successful control of the interfacial bonding of multimaterial systems fabricated by this technique. , Despite the interesting papers dedicated in the recent years to 3D printing process (specially to FDM), there is an aperture to DPPmE and its adaptation to develop innovative FGM devices for medical applications.…”
Section: Introductionmentioning
confidence: 99%